Appropriate Doses of Iron for Treatment of Anemia Amongst Pregnant and Lactating Mothers; Under Five Children; Children in 6-10 Years of Age; Adolescent Girls and Women in Reproductive Age Groups - Krishnapillai, Madhavan Nair; Choudhury, Dripta Roy; Konapur, Archana (Indian Journal of Community Health, 2018)
Iron deficiency is the leading cause of anemia in India. In spite of implementation of a National iron supplementation programme of anemia control, the rate of decline in anemia prevalence has not been satisfactory. To address this issue, a National consultation meeting is being organized by the Ministry of Health and Family Welfare, Government of India, 23-24th April 2018, AIIMS, New Delhi. The purpose of the background document is to facilitate the deliberations of the above meeting. In this document, we discuss the latest progress in studies of iron metabolism, bioavailability, requirement and RDA for Indians. Hepcidin is a circulating peptide hormone secreted by the liver that plays a central role in coordinating the use and storage of iron with iron acquisition. Therefore, we considered it important to review and include trials on modulation of hepcidin during iron supplementation. Further, we made an attempt to review iron supplementation trials in Indian pregnant women and children to sequentially assess the basis for fixing iron dosage. Finally, we made an attempt to apply theoretical basis of computation of iron dose for the age/gender and physiological group for treatment of anemia due to iron deficiency. In the light of the role of hepcidin in iron nutrition, we consider it important to characterize the contextual determinants and establish the iron dosage. We believe that the systemic regulation may not allow the body to store adequate amounts of iron from oral doses in short duration of 100 days. Based on the biology of iron it appears that iron homeostasis leading to assimilation of storage of iron is a very slow process and may require practice of contextual food synergy systems to improve iron content (fortified foods) and bioavailability (vitamin C rich fruits) throughout life cycle.